Reviews (Modern theology, 1999)
Daniel W. Hard, God's Ways with the World: Thinking and Practising Christian Faith Sallie McFague, Super, Natural Christians: How We Should Love Nature Wolfhart Pannenberg, Systematic Theology Volume 3 Miroslav Volf, After Our Likeness: The Church as the Image of the Trinity Michael Battle, Reconciliation: The Ubuntu Theology of Desmond Tutu Philip Clayton, God and Contemporary Science Christopher R. Seitz, Word Without End. The Old Testament as Abiding Theological Witness Louis Dupré, Religious Mystery and Rational Reflection: Excursions in the Phenomenology and Philosophy of Religion Duncan B. Forrester, Christian Justice and Public Policy Emmanuel Levinas, Entre-Nous: On Thinking of the Other